Necrotising Soft Tissue Infections: The Effect of Hyperbaric Oxygen on Mortality. Issue 6 (November 2015) - Devaney, B.; Frawley, G.; Frawley, L.; Pilcher, D. V.
In a single-centre, retrospective, case-controlled study of patients attending the Alfred Hospital in Prahran, Victoria, we assessed the effect of hyperbaric oxygen therapy (HBOT) in reducing mortality or morbidity in patients with necrotising fasciitis (NF) over a 13-year period from 2002 to 2014. A total of three hundred and forty-one patients with NF were included in the study, of whom 275 received HBOT and 66 did not. The most commonly involved sites were the perineum (33.7%), lower limb (29.9%) and trunk (18.2%). The commonest predisposing factor was diabetes mellitus (34.8%). Polymicrobial NF (type 1 NF) occurred in 50.7% and Group A streptococcal fasciitis (type 2 NF) occurred in 25.8% of patients. Mortality was 14.4% overall, 12% in those treated with, and 24.3% in those not treated with, HBOT. ICU support was required in 248 (72.7%) patients. Independent factors impacting on mortality included HBOT (odds ratio [OR] 0.42 [0.22 to 0.83], P =0.01), increased age (OR 1.06 [1.03 to 1.08], P =0.001) and immunosuppression (OR 2.6 [1.23 to 5.51], P =0.01). Mortality was linked to illness severity at presentation, however when adjusted for severity score and need for intensive care management, HBOT was associated with significant reduction in mortality.